2016
DOI: 10.1016/j.molmet.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Microscopy tools for the investigation of intracellular lipid storage and dynamics

Abstract: BackgroundExcess storage of lipids in ectopic tissues, such as skeletal muscle, liver, and heart, seems to associate closely with metabolic abnormalities and cardiac disease. Intracellular lipid storage occurs in lipid droplets, which have gained attention as active organelles in cellular metabolism. Recent developments in high-resolution microscopy and microscopic spectroscopy have opened up new avenues to examine the physiology and biochemistry of intracellular lipids.Scope of reviewThe aim of this review is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
100
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 77 publications
0
100
0
Order By: Relevance
“…1a). For detailed quantitative analysis we co-localized TMEM119 + microglia with BODIPY, a dye that specifically labels neutral lipids and is commonly used to detect lipid droplets 36,37 . We observed that in the aged brain, BODIPY + microglia were abundant in the hippocampus but scarce in other regions ( Supplementary Fig.…”
Section: Microglia Accumulate Lipid Droplets In the Aging Brainmentioning
confidence: 99%
“…1a). For detailed quantitative analysis we co-localized TMEM119 + microglia with BODIPY, a dye that specifically labels neutral lipids and is commonly used to detect lipid droplets 36,37 . We observed that in the aged brain, BODIPY + microglia were abundant in the hippocampus but scarce in other regions ( Supplementary Fig.…”
Section: Microglia Accumulate Lipid Droplets In the Aging Brainmentioning
confidence: 99%
“…coherent anti-stokes Raman scattering, and imaging mass spectrometry, e.g. secondary ion mass spectrometry, could enable the role of specific lipid species in their subcellular localization to be studied in the near future (Daemen et al, 2016).…”
Section: Location Of Lipidsmentioning
confidence: 99%
“…We first focused on lipid-rich tissues such as sebaceous glands, myelin sheath in the brain, and adipose tissues, which showed strong CDL signals and weak CDP signal ( Figure 4F-I and Supplementary Figure 4A). Because the visualization of in situ lipid synthesis dynamics in mouse models had been particularly challenging with previous methods, which mostly capture the static level 37 , here we demonstrate the utility of DO-SRS in studying the development and metabolic homeostasis of the lipid-rich tissues. From those studies, we also gained new insights into mammalian lipogenesis.…”
Section: Visualizing De Novo Lipogenesis and Metabolic Homeostasis Inmentioning
confidence: 87%